(untitled) (AYUSHDHARA, 2024)
Avapeeda nasya is a special procedure described to treat Urdhwajatrugata vikaras in Ayurveda. In this procedure fresh juice (Swarasa) is obtained by squeezing paste of herbs or decoction is used to instil in nostril. Shalakya is special branch of Ayurveda which deals with the diseases above clavicle (Jatru). Aiming for Vyadhi-parimokshana treatment can be done by Sanshamana or Sanshodhan methods. Panchakarma is Shodhana type in which Nasya is a procedure. Acharyas mentioned Nasa hi shirso dwaram, meaning it is the portal to head (for drug administration). To critically appraise and understand the standard Avapeeda Nasya is the focus of my presentation. Procedure of Avapeeda Nasya, its difference from Sneha nasya, mode of action and other norms are discussed in the paper. Avapeeda Nasya acts as Shodhana and Shamana. When abundance of Doshas are present Tikshna dravyas are used to clear the channels (Sroto-Shodhana), when Doshas are mild or moderate Shamana dravyas are used. To expel Doshas from upper body, Nasa is the portal to Shiras. The active principle of the medicine used in Nasya reaches Shringataka marma (Sira marma) and is distributed to Moordha- Netra – Shrotra – Kantha and thereby expel morbid Doshas. Drug reaches the target area by crossing nasal mucosa, thereafter transported via nerve tract, systemic circulation or by lymphatics. Intra-nasally administered drug has higher bioavailability as it avoid first pass mechanism at liver and evade BBB.